Efisiensi Produksi Industri Rumah Tangga Kacang Tanah Sangrai Dengan Pendekatan Data Envelopment Analysis - Ahmad Burhan; Ainul Haya Mutia; Iis Ismawati; Safina Maulida; Soraya Nusafayat; Pitri Yandri (Indonesian Journal of Economics Application (IJEA), 2018)
Efficiency on every type of business entity is important in order to develop a business with the main purpose is increasing profit. This research aims to analyze the efficiency of the production roasted peanut household industry with an approach to Data Envelopment Analysis. The results show that the industry has reached a value proportional efficiency. Another research findings are we get any difficulties in obtain accurate data because the industry did not do adequate financial record. On that situation, the policy recommendation that can be implemented by the industry is recording financial report.